Effect of postoperative radiotherapy for free flap volume changing after tongue reconstruction. - Yamazaki, Masae; Suzuki, Taiki; Hiraga, Chiho; Yoshida, Yoshifumi; Baba, Akira; Saitou, Hirokazu; Ogane, Satoru; Fujii, Takako; Takano, Masayuki; Katakura, Akira; Tanaka, Ichiro; Nomura, Takeshi; et al. (Oral Radiology, 2021)
Objective: The purpose of this study was to evaluate the effect of postoperative radiotherapy (RT) on temporal volume changes with a cutaneous free flap (CF) and a myocutaneous free flap (MCF). Methods: The subjects were 24 men and 11 women (mean age, 50.5 ± 15.5 years) with tongue or floor of mouth cancer. Twenty-seven cases of CF and eight cases of MCF were selected. The flap volume change of the reconstructed tongue was calculated using computed tomography (CT) images taken immediately and at one year postoperatively using the DICOM image processing software OsiriX®. Results: The reduction rate in flap volume at one year postoperatively was 82.0 ± 15% in CF without RT, 70.3 ± 26.1% in CF with RT, 88.5 ± 14.7% in MCF without RT, and 99.5 ± 16% in MCF with RT. The MCF volume was significantly higher compared to the CF volume. Although postoperative RT reduced the CF volume by 30%, there was only a slight reduction in the MCF volume. Conclusions: We evaluated the effect of postoperative RT on volume reduction in 35 cases of the reconstructed tongue with CF and MCF using a computer-assisted volume rendering technique. In this study, the effect of RT on volume reduction was different between the CF and MCF.